Analisa Faktor Operasional, Tarif, Fasilitas dan Keselamatan Terhadap Pelayanan Pemanduan di PT Pelabuhan Indonesia (Persero) IV Bitung Sulawesi Utara - Asmawati, Asmawati; Sumantri, Andar Sri; Sulistyowati, Sulistyowati; Sutini, Sutini (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to determine the Analysis of Operational Factors, Tariffs, Facilities and Safety Against Guidance Services at PT. Port of Indonesia (Persero) Regional 4 pelabuhan Bitung This research was conducted on employees of the Shipping Agency working area of ​​Tanjung Redeb as a population. Data was collected through the methods of Observation, Literature Study, Interview, Documentation and Questionnaire. The analytical technique used is based on the results of research and multiple analysis with the help of the SPSS V.26. Here’s the result from research of regression : Y = -0,219 + 0,308X1 + 0,200X2 + 0,192X3 + 0,349X4 + µ. The multiple linear regression equation can be seen that the most dominant variable influencing the guidance is the safety variable with a regression coefficient of 0.349. With the coefficient of determination (Adjusted R square) the results obtained are 0.837 or 83.7%, which means that the guidance at PT. Port of Indonesia (Persero) Regional 4 Pelabuhan Bitung is influenced by operational variables, tariffs, facilities and safety which is 83.7% and other factors that affect the guidance of PT. Port of Indonesia (Persero) Regional 4 Pelabuhan Bitung is 16.7%. Thus the results of the study indicate that Operations, Tariffs, Facilities and Safety have a positive and significant effect on the PT. Port of Indonesia (Persero) Regional 4 Pelabuhan Bitung.